2015
DOI: 10.1021/la504978r
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Templated Biomimetic Silica Nanoparticles

Abstract: Biomimetic silica particles can be synthesized as a nanosized material within minutes in a process mimicked from living organisms such as diatoms and sponges. In this work, we have studied the effect of bovine serum albumin (BSA) as a template to direct the synthesis of silica nanoparticles (NPs) with the potential to associate proteins on its surface. Our approach enables the formation of spheres with different physicochemical properties. Particles using BSA as a protein template were smaller (∼250–380 nm) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Since then, proteins with redox properties have been utilized as versatile nanoreactors for bottom‐up fabrication of a variety of protein‐conjugated nanocrystals owing to the reduction potentials provided by redox amino acids of proteins . In addition to the nanocrystals, proteins were also viable for the synthesis of silica‐based biomimetic nanoparticles, suggesting its versatility for various source of inorganic precursors. On the other hand, the surface topology and residues of the protein are noncontinuous, resulting in discontinued distribution of reduction potentials in the cage.…”
Section: Recent Progress In Functional Macromolecule‐enabled Colloidamentioning
confidence: 99%
“…Since then, proteins with redox properties have been utilized as versatile nanoreactors for bottom‐up fabrication of a variety of protein‐conjugated nanocrystals owing to the reduction potentials provided by redox amino acids of proteins . In addition to the nanocrystals, proteins were also viable for the synthesis of silica‐based biomimetic nanoparticles, suggesting its versatility for various source of inorganic precursors. On the other hand, the surface topology and residues of the protein are noncontinuous, resulting in discontinued distribution of reduction potentials in the cage.…”
Section: Recent Progress In Functional Macromolecule‐enabled Colloidamentioning
confidence: 99%
“…Barnacle Megabalanus rosa (MRCP20) protein has also shown promising results in the self-assembly of calcite crystals [88]. A few studies have also shown degrees of success producing silica nanoparticles and materials using protein-assisted synthesis techniques [89,90,91]. Coccolithophore proteins offer huge potential for creating novel “ smart interface ” biomaterials for bone repair.…”
Section: Translations Into Strategies For Bone Repairmentioning
confidence: 99%
“…To fruitfully put this lesson to use, bioinspired matrices have been developed such as biosilica. The definition of biosilica, just like that of biomaterials in general, varies between silica/materials that are formed in nature by living organisms (aka biogenic materials, which are more appropriately referred to as biosilica) and silica/materials that is synthesized in the lab by bioinspired reactions, using molecules from the living organism or their derivatives [32][33][34], to mimic the "natural conditions" (bio-inspired silica). Hereon, for simplicity we will refer to either species as biosilica, as the origin of the material is clearly described along with the experimental details.…”
Section: Biosilica -A Lesson To Be Learnedmentioning
confidence: 99%